Effect of thermal history on high‐valence chromium ion dissolution in merwinite (3CaO·MgO·2SiO2). Issue 6 (20th February 2018) - Suzuki, Masanori; Umesaki, Norimasa; Okajima, Toshihiro; Tanaka, Toshihiro
Abstract: Solubility and local structure of transmission elements in calcium silicate compounds has not been well understood. We investigate the local structure of chromium ions dissolved in merwinite (3CaO·MgO·2SiO2 ) of a monoclinic crystal structure. The acceptance of doping elements into merwinite has not been reported before. We found that chromium ions are soluble in merwinite in air and that chemical valence of the dissolved Cr ions varies with annealing temperature. The absorption edge in the x‐ray absorption near edge structure (XANES) of Cr‐doped merwinite indicated that octahedrally coordinated Cr 3+ ions were mainly formed when annealed at 1673 K in air. A pre‐edge peak was also detected, indicating the existence of tetrahedrally coordinated high‐valence Cr ions. Conversely, through annealing of merwinite at 1123 K in air, tetrahedrally coordinated Cr 6+ ions were found to be the main form of chromium. XANES spectra simulated by first‐principle calculations were used to explain the structural features in the observed spectra. We propose the coexistence of Cr 3+ ions in octahedral Mg 2+ sites and high‐valence Cr ions in tetrahedral Si 4+ sites. In addition, a change in the chromium ion oxidation state in tetrahedral coordination sites was suggested by XANES spectroscopy of Cr‐doped merwinite synthesized at 1673 K and reannealed at 1123 K.